2020
DOI: 10.1038/s41598-020-69318-y
|View full text |Cite|
|
Sign up to set email alerts
|

Comparing the visual outcome, visual quality, and satisfaction among three types of multi-focal intraocular lenses

Abstract: This study compared the visual outcome, visual quality, and satisfaction following implantation of the Mix-and-Match bifocal IOLs (+ 2.75 D and + 3.25 D add power Tecnis Multifocal Model), EDOF IOL (Tecnis Symfony IOL), and Trifocal IOL (FineVision PodFT, PhysIOL). All outcomes were compared among the three groups. The manifest refraction indicated that the EDOF group had significantly higher myopic spherical equivalent values than did the others. In the terms of visual acuity, there were no significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 19 publications
4
24
0
Order By: Relevance
“…The current study showed good distant, intermediate and near uncorrected visual acuity results that were comparable to the visual acuity outcomes of both multifocal and EDOF IOLs that were previously reported. 11,20,2326 The UDVA result of the current study ( −0.01 ± 0.04 logMAR) was found comparable to the UDVA results of ZKB00 reported by Tarib et al 25 (0.14 ± 0.14 logMAR), Yang et al 26 ( −0.02 ± 0.10 logMAR) and Turhan et al 27 ( −0.05 ± 0.06 logMAR). The UDVA result of the current study appears to be in accordance with the UDVA result of EDOF IOL that was reported by Kohnen et al ( −0.02 ± 0.071 logMAR) and Concerto study group 28 (0.03 ± 0.09 logMAR).…”
Section: Discussionsupporting
confidence: 88%
“…The current study showed good distant, intermediate and near uncorrected visual acuity results that were comparable to the visual acuity outcomes of both multifocal and EDOF IOLs that were previously reported. 11,20,2326 The UDVA result of the current study ( −0.01 ± 0.04 logMAR) was found comparable to the UDVA results of ZKB00 reported by Tarib et al 25 (0.14 ± 0.14 logMAR), Yang et al 26 ( −0.02 ± 0.10 logMAR) and Turhan et al 27 ( −0.05 ± 0.06 logMAR). The UDVA result of the current study appears to be in accordance with the UDVA result of EDOF IOL that was reported by Kohnen et al ( −0.02 ± 0.071 logMAR) and Concerto study group 28 (0.03 ± 0.09 logMAR).…”
Section: Discussionsupporting
confidence: 88%
“…Although we identified some studies to evaluate the subjective depth of focus of bifocal or trifocal IOLs, there is still insufficient research to investigate subjective the depth of focus in eyes with EDOF IOLs using defocus curves, so the results of those studies cannot be directly compared to ours. 13 , 16 Firstly, we adopted the blur tolerance criterion at 0.2 logMAR, other studies used more subjective criteria. Assessing the subjective depth of focus of AT LISA tri IOLs, Barisic reported the mean depth of focus of 2.59 D, having assumed the blur tolerance criterion of 20/30.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 However, other studies showed no significant differences in binocular UIVA between EDOF IOLs and trifocal IOLs. 2,13 In a mix-and-match bilateral implantation of EDOF IOLs (AT LARA 829 MP IOL, Carl Zeiss Meditec AG) and trifocal IOLs (AT LISA tri 839 MP IOL, Carl Zeiss Meditec AG) study, the results illustrated good unaided visual acuity for both intermediate and near distance. 16…”
Section: Discussionmentioning
confidence: 97%
“…14,15 However, other studies showed no significant differences in binocular UIVA between EDOF IOLs and trifocal IOLs. 2,13 In a mix-and-match bilateral implantation of EDOF IOLs (AT LARA 829 MP IOL, Carl Zeiss Meditec AG) and trifocal IOLs (AT LISA tri 839 MP IOL, Carl Zeiss Meditec AG) study, the results illustrated good unaided visual acuity for both intermediate and near distance. 16 This current study demonstrated that mix-and-match implantation of an EDOF-IOL in the dominant eye and a diffractive bifocal IOL in the nondominant eye exhibited excellent binocular visual acuities at all distances.…”
Section: Discussionmentioning
confidence: 99%